Anionic hydrogel fabricated with metal nanoparticles: highly efficient and easily recyclable catalysts. Issue 4 (2nd October 2021) - Naeem, Hina; Ajmal, Muhammad; Khan, Saba Zamurad; Ashiq, Muhammad Naeem; Siddiq, Muhammad
ABSTRACT: Herein, we synthesized poly(methacrylic acid) [p(MAAc] hydrogels by an effective and simple free radical polymerization process and then silver, cobalt, and their bimetallic nanoparticles (NPs) were synthesized by using p(MAAc) as a template. Upon loading of Ag (I) and Co (II) ions by p(MAAc) hydrogels from their corresponding aqueous salt solutions, these metal ions loaded hydrogels were then treated with sodium borohydride, a reducing agent to obtain corresponding metal nanoparticles (NPs) within the hydrogel network. Hydrogels and metal nanoparticle containing composite hydrogels were analyzed in detail by Transmission Electron Microscopy, X-ray Diffraction, Fourier Transform Infra-red spectroscopy, UV-Vis Spectrophotometry and Thermal Gravimetric Analysis techniques. Synthesized p(MAAc)-M hydrogel composites were utilized as catalysts for degradation of some harmful organic residual dyes like Eosin Y (EY), methyl orange (MO) along with reduction studies of some nitro aromatic compounds including 2-nitrophenol (2-NP), 4-nitrophenol (4-NP), 4-nitroaniline (4-NA) to their respective amino phenolic compounds from contaminated water. Above all, we also report simultaneous degradation studies of a dye EY and a nitro compound, 4-NP catalyzed by p(MAAc)-Ag composite hydrogel. The parameters such as nature of metal, catalyst amounts, temperature, water samples from different resources, and reusability of prepared hydrogel-metal nanoparticle nanocomposite catalysts were also investigated.